Three new species of Coecobrya (Collembola: Entomobryidae) from caves in the Thai Peninsula - Nilsai, Areeruk; Jantarit, Sopark; Satasook, Chutamas; Zhang, Feng (Zootaxa, 2017)
Three new species of the genus Coecobrya are described from caves in the Thai Peninsula for the first time: C. cavicta sp. nov. and C. polychaeta sp. nov. from Satun Province, and C. chumphonensis sp. nov. from Chumphon Province. These species differ in antennal length, clypeal chaetae, labial palp, sublobal chaetae of maxillary outer lobe, labial and postlabial chaetae, claw, ventral tube, manubrial plaque, and dorsal cephalic and tergal chaetotaxy. They are similar to C. annulata Zhang, Bedos & Deharveng, 2016 but differ from the latter in the combination of antennal length, claw and dorsal chaetotaxy. DNA barcoding COI sequences are provided for two species and three populations and key to the Thai species is also given. One population, which exhibits a great genetic distance (0.219–0.239) and minor but stable morphological differences from C. polychaeta sp. nov., cannot be accepted as a full species as the evidence is insufficient.